An interaction between BRG1 and histone modifying enzymes mediates lipopolysaccharide‐induced proinflammatory cytokines in vascular endothelial cells. Issue 8 (19th March 2019) - Zhang, Yuanyuan; Yuan, Yibiao; Li, Zilong; Chen, Huan; Fang, Mingming; Xiao, Pingxi; Xu, Yong
Abstract: Vascular inflammation is the culprit for a host of human diseases. The underlying mechanism, however, is not definitively elucidated. In the present study, we investigated the interplay between different epigenetic factors during lipopolysaccharide (LPS) induced synthesis of proinflammatory cytokines in cultured vascular endothelial cells. We report that in response to LPS treatment, NF‐κB was deplored to its target promoters along with the chromatin remodeling protein BRG1. Paralleling these changes trimethylated H3K9 became erased from while trimethylated H3K4 started to accumulate on the NF‐κB target promoters. Further analysis revealed that LPS stimulation resulted in sequential recruitment of the H3K9 tri‐demethylase JMJD2A and the H3K4 trimethyltransferase SET1A to the NF‐κB target promoters. JMJD2A mediated–H3K9 demethylation served as a prerequisite for SET1A to bind to the NF‐κB target promoters. Both JMJD2A and SET1A were essential for LPS‐induced transactivation of proinflammatory cytokines by sustaining the binding of NF‐κB. Of key importance, BRG1 coordinated the sequential recruit of and the interplay between JMJD2A and SET1A. In conclusion, our data unveil a novel epigenetic mechanism that contributes to LPS‐induced vascular inflammation. Abstract : In response to lipopolysaccharide (LPS) stimulation, sequential recruitment of BRG1 and histone modifying enzymes mediates activation of proinflammatory cytokines in vascular endothelial cells. Deficiencies in various epigenetic factors result in attenuated NF‐kB recruitment and dampened proinflammatory response.